GROWTH, YIELD AND WATER USE OF MAIZE AS INFLUENCED BY DRIP IRRIGATION SCHEDULES AND NITROGEN LEVELS - Y. DEEPTHI KIRAN*, V. SUMATHI; G. PRABHAKARA REDDY (The Journal of Research ANGRAU, 2019)
The field experiment was conducted for two consecutive years (2013-14 and 2014-15) to evaluate the yield and economic returns from maize under different irrigation schedules and nitrogen levels. The experiment was laid out in split-plot design and replicated thrice by applying four irrigation schedules under the mainplot and three nitrogen levels under subplot. The growth parameters and yield of maize were found superior with weekly check basin irrigation, however, were on par with drip irrigation at 0.9 IW/CPE ratio. Among the nitrogen levels tried, 240 kg N ha-1 recorded higher growth and yield. The interaction between the irrigation schedules and nitrogen levels indicated the better growth parameters and higher yield with irrigation scheduled either by weekly check basin method or through drip irrigation at 0.9 IW/CPE ratio along with 240 kg N ha-1. The water use efficiency was also higher with drip irrigation scheduled at 0.9 IW/CPE ratio. The results revealed that maize crop can be grown economically with the irrigations scheduledat 0.9 IW/CPE ratio through drip irrigation along with 240 kg N ha-1.